Five children with deletions of 1p34.3 encompassing AGO1 and AGO3 - Tokita, Mari J (Eur J Hum Genet, 2015)
Small RNAs (miRNA, siRNA, and piRNA) regulate gene expression through targeted destruction or translational repression of specific messenger RNA in a fundamental biological process called RNA interference (RNAi). The Argonaute proteins, which derive from a highly conserved family of genes found in almost all eukaryotes, are critical mediators of this process. Four AGO genes are present in humans, three of which (AGO 1, 3, and 4) reside in a cluster on chromosome 1p35p34. The effects of germline AGO variants or dosage alterations in humans are not known, however, prior studies have implicated dysregulation of the RNAi mechanism in the pathogenesis of several neurodevelopmental disorders. We describe five patients with hypotonia, poor feeding, and developmental delay who were found to have microdeletions of chromosomal region 1p34.3 encompassing the AGO1 and AGO3 genes. We postulate that haploinsufficiency of AGO1 and AGO3 leading to impaired RNAi may be responsible for the neurocognitive deficits present in these patients. However, additional studies with rigorous phenotypic characterization of larger cohorts of affected individuals and systematic investigation of the underlying molecular defects will be necessary to confirm this.